KETERKAITAN PERTUMBUHAN PERUSAHAAN, ENTREPRENEURIAL GOAL COMMITMENT DAN SELF EFFICACY DALAM MODEL PENELITIAN ENTREPRENEURSHIP - Agung Ulupui, I Gusti Ketut (Buletin Studi Ekonomi, 2013)
The phenomenon of entrepreneurship as a driver of micro, small and medium enterprises (MSMEs) emerged rapidly. Business growth in this paper is stated as a success or performance. Meanwhile the success or the performance from a person in a line of work determined by the competence, professionalism, and commitment to the field practiced. This paper provides an alternative model of research on the influence of goal entrepreneurship self-efficacy as a moderation variable to relationship commitment and growth in particular small and medium enterprises (SMEs)
Keywords: self efficacy, goal commitment, companies growth, SMEs